Hybrid Natural Fiber Composites of Polylactic Acid Reinforced with Sisal and Coir Fibers - Wipoo Sriseubsai; Ariya Praemettha (Polymers, 2024)
, outperforming other mixtures and pure PLA in the mechanical properties. Additionally, water absorption tests showed that reinforcement with sisal and coir fibers increased both water absorption and stability over 60 h.
Keywords: Natural Fiber Reinforced Composites; biodegradable polymer synthesis and properties; Additive Manufacturing and 3D Printing Technologies